(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
Since Hungary joined the European union according to the Union’s guidelines the Hungarian children can learn in Austrian schools with the same terms and conditions as Austrian students. As a result, the number of students who go to school in Austrian instead of Hungary started to increase, parallel to this there are more and more Hungarian parents who decide to take their children to Austrian kindergartens. The parents’ motives when choosing a kindergarten or a school are definitely for their children to learn languages and to become bilingual. During the research on the children’s becoming bilingual, we’ve looked for an answer for which way of becoming bilingual is happening since the children are living in a Hungarian speaking environment but they are in a German speaking environment in the kindergarten and in the school; how long does it take them to master the German language; how is their use of language is developing and if problems occur when changing the communication code.